Microsoft Form as a Scaffolding-Based Geometry Learning Media in Online Learning - Zukhrufurrohmah, Zukhrufurrohmah; Dintarini, Mayang (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
Geometry learning outcomes are lower than other mathematical fields, so media are needed to overcome students' difficulties solving geometry problems. This study aims to produce a product in online learning media for scaffolding-based geometry materials using Microsoft Form. There are three stages of Research and Development research, namely preliminary research, prototyping, and assessment. The validation results show that the scaffolding-based media developed is valid with a percentage of 76%. Field notes show that the scaffolding-based media developed can be used easily and practically by lecturers and students. A positive response was also given by 30 third semester students who used media in learning circle material. The test results showed that 73% of the total number of students scored no less than 70. Therefore, the scaffolding-based media developed was declared valid, practical, and effective in learning circle material.Hasil belajar geometri lebih rendah dibandingkan bidang matematika lainnya, sehingga diperlukan media untuk mengatasi berbagai kesulitan siswa dalam menyelesaikan permasalahan geometri. Penelitian ini bertujuan untuk menghasilkan produk berupa media pembelajaran online materi geometri berbasis scaffolding menggunakan Microsoft Form. Tiga tahapan penelitian Research and Development penelitian ini yaitu penelitian pendahuluan, pembuatan prototipe, dan asesmen. Hasil validasi menunjukkna bahwa media berbasis scaffolding yang dikembangkan valid dengan persentase 76%. Catatan lapangan menunjukkan media berbasis scaffolding yang dikembangkan dapat digunakan dengan mudah dan praktis oleh dosen maupun mahasiswa. Respon positif juga diberikan oleh 30 mahasiswa semester 3 yang menggunakan media pada pembelajaran materi lingkaran. Hasil tes menunjukkan bahwa 73% dari jumlah mahasiswa mendapatkan nilai tidak kurang dari 70. Oleh karena itu media berbasis scaffolding yang dikembangkan dinyatakan valid, praktis dan efektif dalam pembelajaran materi lingkaran.